THE NEED FOR INVESTMENT IN THE FORMATION AND DEVELOPMENT OF THE INNOVATIVE ENVIRONMENT (Intent Research Scientific Journal, 2023)
The article analyzes the fact that today most of the countries of the world are facing the task of transitioning to a science-based innovative economy, and are developing medium and long-term strategies for creating, selling and using the results of scientific and technical activities. Such strategies are considered the main condition of sustainable economic growth, in recent years, great attention has been paid to the development of scientific institutes, leading scientific schools and innovative research in Uzbekistan, and as world experience shows, there is no other alternative way of social development than innovative development